Psychological consequences of perceived job insecurity among permanent and fixed-term employees: a role of workplace control - Maslić Seršić, Darja (2007)
The last decade has been characterized by profound transformations of working life in Croatia. From the workers’ perspective, this has been reflected in increasing job insecurity and decreasing work-role depended sources of certainty. Although this phenomenon is not empirically studied, there is a consensus among politicians, economics and citizens in Croatia that perceived job insecurity is rather high. On the contrary, such consensus does not exist when considering its motivational and health impacts. Consequently, practical and theoretical aims of the study were defined: (1) To search perceived job insecurity and its relation to the work attitudes and wellbeing among Croatian employees of different demographic and work characteristics ; (2) To test a mediating role of perceived workplace control on the consequences of job insecurity. Perceived job insecurity and workplace control were measured by the six-item scale of global job insecurity (Sverke et al. 2004) and the three-item scale of powerlessness (Ashford et al, 1989). A convenience sample of 620 respondents employed in various organizations, with permanent and fixed-term contracts, was used for data collection. Results show significant differences in experienced job insecurity between the groups of different work characteristics: a higher occupational status and employment in larger organizations were related to less job insecurity. When demographic and work characteristics were statistically controlled, perceived job insecurity significantly predicted employees’ affective organizational commitment, job and life satisfaction, but was mediated by perceived powerlessness. Observed relations were moderated by the type of work contract showing a stronger impact of perceived powerlessness in the measured outcomes prediction among the employees with fixed-term contracts.